Modelagem das perdas de água por evaporação e arraste de sprays de placa oscilante - Colombo, Alberto (2015)
Among several factors that exert influence on evaporation and wind drift losses (EWL), the wind has attracted researcher’s attention in scientific studies. In this context, the objectives of this study were: i) to determine EWL that occurred in eleven field tests with a center pivot system; ii) to develop a model to estimate EWL in function of predictor variables; iii) to evaluate prediction models available in literature for estimation of EWL from data acquired in the field trials. The tests were carried out along a 48-m span located between the fourth and fifth tower of a center pivot of 432.57 m in length, equipped with a model of rotating spray plate sprinklers known as I-Wob. Evaporation and wind drift losses were simulated using five empirical models. Additionally, a specific model was developed for the operational and meteorological conditions observed in this study. It was found that the empirical models presented unsatisfactory performance indices when they were tested for the operational and meteorological conditions observed in this study. The errors obtained from the adjusted model were lower than those observed when using the existing models. Thus, this model can be used for conditions similar to those experienced in this study.